2017
DOI: 10.1002/cjce.22840
|View full text |Cite
|
Sign up to set email alerts
|

High catalytic efficiency of Pd nanoparticles immobilized on TiO2 nanorods‐coated ceramic membranes

Abstract: In this work, we designed and constructed an efficient and reusable membrane catalyst by loading palladium (Pd) nanoparticles on TiO2 nanorods (NRs)‐coated ceramic membrane. The morphology and structure analysis show that the TiO2 NRs with a width of 200 nm–1000 nm and a length of about 4000 nm can be successfully synthesized on the ceramic membrane by a two‐step hydrothermal method. The Pd nanoparticles with an average particle size of 4 nm can be uniformly distributed on the TiO2 NRs‐coated ceramic membrane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…TiO 2 nanorod arrays on sheet Al 2 O 3 ceramic membranes (circular, 3.2 cm in diameter, 1.6 mm in thickness and 30% in porosity) were obtained via the following two-step hydrothermal method. 26 Twenty mL of concentrated hydrochloric acid (Analytical Reagent, This article is protected by copyright. All rights reserved.…”
Section: Synthesis Of Tio 2 Nanorods and Branched Tio 2 Nanorods On Ceramic Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 nanorod arrays on sheet Al 2 O 3 ceramic membranes (circular, 3.2 cm in diameter, 1.6 mm in thickness and 30% in porosity) were obtained via the following two-step hydrothermal method. 26 Twenty mL of concentrated hydrochloric acid (Analytical Reagent, This article is protected by copyright. All rights reserved.…”
Section: Synthesis Of Tio 2 Nanorods and Branched Tio 2 Nanorods On Ceramic Membranesmentioning
confidence: 99%
“…Greater than 90% of the PNP was reduced within 4 hours using a single reaction step, and deactivation was observed after consecutive catalytic cycles. Our group 26 successfully demonstrated that the use of TiO 2 nanorod-functionalized ceramic membranes is an effective approach for enhancing the loading amount of Pd and the corresponding catalytic activity. However, the catalytic membranes obtained when used directly in a batch reactor could not achieve continuous conversion of PNP.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, noble metal nanoparticles can be used as highly efficient catalysts, and these nanoparticles were studied by several research groups. [ 23–26 ]…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, noble metal nanoparticles can be used as highly efficient catalysts, and these nanoparticles were studied by several research groups. [23][24][25][26] The current work describes the one-pot green synthesis of silver nanoparticles supported on calcium alginate (CA-Agnp) beads, the characterization of CA-Agnp, and the application as a catalyst for the reduction of p-nitrophenol (p-NP) to p-aminophenol (p-AP) using sodium borohydride as a reducing agent. There are two important ways of preparing CA-Agnp beads, as reported in the literature: (a) the absorption of Ag + ion in the previously prepared beads followed by reduction to silver nanoparticles (Agnp) by some external processes and (b) the preparation of colloidal solution of sodium alginate and Agnp followed by conversion into beads.…”
mentioning
confidence: 99%
See 1 more Smart Citation